2019
DOI: 10.1002/ehf2.12457
|View full text |Cite
|
Sign up to set email alerts
|

MitraClip improves cardiopulmonary exercise test in patients with systolic heart failure and functional mitral regurgitation

Abstract: Aims The aim of this study is to evaluate changes in cardiopulmonary exercise test (CPET) after percutaneous mitral valve repair (PMVR) with MitraClip in patients with heart failure with reduced ejection fraction who are potentially candidates for heart transplantation or destination left ventricular assist device. Methods and results Prospective registry of all consecutive patients with heart failure with reduced ejection fraction and functional mitral regurgitation (MR) underwent elective PMVR between Octobe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…And regarding patients with advanced HF, COAPT showed as well that MitraClip can lead to a reduction in the heart transplant or LVAD implantation rate. This finding, together with other positive data coming from registries, such as reverse remodeling, decrease in arrhythmic burden or improvement in O 2 consumption may prompt the indication in patients with LVD and advanced heart failure (36,(39)(40)(41)(42).…”
Section: Percutaneous Edge-to-edge Mitral Valve Repair (Pmvr)mentioning
confidence: 60%
“…And regarding patients with advanced HF, COAPT showed as well that MitraClip can lead to a reduction in the heart transplant or LVAD implantation rate. This finding, together with other positive data coming from registries, such as reverse remodeling, decrease in arrhythmic burden or improvement in O 2 consumption may prompt the indication in patients with LVD and advanced heart failure (36,(39)(40)(41)(42).…”
Section: Percutaneous Edge-to-edge Mitral Valve Repair (Pmvr)mentioning
confidence: 60%
“…Patients with functional MVR who underwent TEER showed an improvement in CPET parameters, including the peak VO 2 , likely due to the increase in anterograde stroke volume, decrease in pulmonary pressures, and reverse remodelling of the LV [81,82]. On the contrary, it has been reported that individuals affected by degenerative or secondary MVR treated with TEER did not exhibit an increase in peak VO 2 despite the improvement in cardiac output [83].…”
Section: Percutaneous Mitral Valve Interventionsmentioning
confidence: 94%
“…On top of the MITRA‐FR and the COAPT trials, which mainly focused on pMVR‐induced changes in prognosis, 6,7 several other studies were published on the efficacy of pMVR. Overall, these studies suggest that pMVR treatment is associated with an improvement in symptoms, quality of life, functional status and, in some but not all studies, exercise capacity 8–12 . Indeed, although MR directly impairs exercise performance, 13 both the COAPT and the MITRA‐FR trials reported a null effect of pMVR on the 6‐min walk test (6MWT) 6,7,14 .…”
Section: Introductionmentioning
confidence: 92%
“…Overall, these studies suggest that pMVR treatment is associated with an improvement in symptoms, quality of life, functional status and, in some but not all studies, exercise capacity. 8 , 9 , 10 , 11 , 12 Indeed, although MR directly impairs exercise performance, 13 both the COAPT and the MITRA‐FR trials reported a null effect of pMVR on the 6‐min walk test (6MWT). 6 , 7 , 14 Differently, several other studies suggested an improved exercise performance, 11 , 15 assessed in the great majority of reports by 6MWT.…”
Section: Introductionmentioning
confidence: 99%